Analisis Manajemen Risiko Kepemimpinan Pada PT Asuransi Raksa Pratikara Indonesia - Gunawan, Risma (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of leadership risk management at PT Asuransi Raksa Pratikara Indonesia. In the midst of the dynamic and uncertain development of the insurance industry, companies are required to have a risk management system that is not only formal, but also effective as a whole. The results of the study show that the company has adopted a risk management framework based on ISO 31000:2018 through the formation of special units, HR training, and internal control. However, the approach applied is still reactive and not fully strategic. Leadership involvement in the risk mitigation process and decision making is still limited, so that the spread of a risk-aware culture is not optimal at all levels of the organization. Strengthening the role of risk-based leadership is needed so that the company can be more adaptive and sustainable in facing future business challenges.